Preparation of steel substrates before application of paints and related products - Surface roughness characteristics of blast-cleaned steel substrates. Part 3: Method for the calibration of ISO surface profile comparators and for the determination of surface profile. Focusing microscope procedure (BSI, 2012)
Steels, Surfaces, Blast-cleaning, Mechanical cleaning, Profile measurement, Surface-roughness measurement, Comparators, Painting, Test equipment, Calibration, Replica techniques, Surface properties, Surface treatment, Cleaning, Roughness (surface), Abrasive processes